2021
DOI: 10.21037/apm-20-2109
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pudendal nerve block for postoperative analgesia of hemorrhoids: a systematic review of 7 randomized controlled trials

Abstract: Pudendal nerve block (PNB) is one of the common anesthesia methods, which has been widely applied in postoperative analgesia of hemorrhoids in recent years. To analyze the effectiveness and safety of PNB on postoperative analgesia of hemorrhoids, we conducted a systematic review of 7 randomized controlled trials (RCT) searched from PubMed, Embase, Web of Science, the Cochrane Central Register of Controlled Trials (CENTRAL), the China Network Knowledge Infrastructure (CNKI), the Wan Fang Database and Chinese Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A meta-analysis not only confirmed the highly beneficial safety of PNBs but also showed that the incidence of nausea and vomiting were significantly reduced ( 10 ). PNBs were also reported to reduce the incidence of urinary retention ( 11 ), which is a relatively common complication after hemorrhoid surgery that may hinder outpatient treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis not only confirmed the highly beneficial safety of PNBs but also showed that the incidence of nausea and vomiting were significantly reduced ( 10 ). PNBs were also reported to reduce the incidence of urinary retention ( 11 ), which is a relatively common complication after hemorrhoid surgery that may hinder outpatient treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple randomized trials have been published on PNBs, confirming a longer analgesic duration and lower incidence of complications compared with the abovementioned drugs ( 8 , 9 ). Although some systematic reviews and meta-analyses support the analgesic effect of PNBs in hemorrhoid surgery ( 10 , 11 ), most of them are based on low-quality research data.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a recent comparative cohort study by Behrenbruch et al suggest that submucosal LA reduces periprocedural analgesic requirement and time to discharge, however, this study was not randomised and may have been subject to bias 12. PNB is well researched in the context of surgical haemorrhoidectomy, and is considered best practice,13 14 but its efficacy in RBL has not been examined.…”
Section: Introductionmentioning
confidence: 95%
“…The review of four randomised controlled trials did not look at surrogate measures of post-procedural pain such as analgesia use and time-to-discharge and was limited by the small sample sizes and heterogeneity of included trials. Additionally, although several meta-analyses have studied the efficacy of PNB in haemorrhoidectomies [ 11 , 12 ], no reviews have included participants who have received a PNB for RBL. There is a need for high-quality research to standardize and optimise analgesia in patients undergoing this common procedure.…”
Section: Introductionmentioning
confidence: 99%